Child Marriage in Chepang Community of Ichachhakamana Rural Municipality, Chitawan, Nepal - Bhattrai, Samjhana Wagle; Acharya, Chiranjivi (Chaturbhujeshwar Academic Journal, 2024)
This article examines the issue of child marriage within the Chepang community of Ichchhakamana Rural Municipality in Chitawan. The research employed primary and secondary data, applying quantitative and qualitative analytical methods. The legal framework in Nepal prohibits marriage for individuals under the age of 20. However, a significant majority, exceeding 90 per cent, of the surveyed individuals were found to have entered into marriage before reaching this age limit. Key contributors to child marriage identified in the study include poverty, insufficient awareness, and the influence of older individuals. The occurrence of child marriage presents considerable risks during the adolescent years, a time when individuals often become increasingly curious about sexual health and relationships. Therefore, awareness campaigns should focus primarily on this demographic. To effectively address the challenge of child marriage, it is vital to emphasize educational and awareness programs. Furthermore, the strict enforcement of existing laws is essential in the pursuit of eliminating child marriage.